Development of a critical appraisal tool to assess the quality of cross-sectional studies (AXIS) - Downes, Martin J.; Brennan, Marnie L.; Williams, Hywel C.; Dean, Rachel S. (BMJ Publishing Group, 2016)
Objectives: The aim of this study was to develop a critical appraisal (CA) tool that addressed study design and reporting quality as well as the risk of bias in cross-sectional studies (CSSs). In addition, the aim was to produce a help document to guide the non-expert user through the tool.